"Even if it doesn't come, you should be prepared": Natural hazard perception, remoteness, and implications for disaster risk reduction in rural Fiji. (September 2020) - Pearce, Tristan; Currenti, Renee; Doran, Brendan; Sidle, Roy; Ford, James; Leon, Javier
Highlights: Preparation is key to surviving a disaster and minimising harm. Local perceptions of risk, worldviews and beliefs influence disaster preparedness. Past experience with less-severe events can contribute to complacency. Climate-proofing homes should include new and traditional construction techniques.